Prudential Center Tower at 800 Boylston Street, ca. 1970 - Unknown (Tufts Archival Research Center, 2005)
Street-level view of the Prudential Center Tower, located at 800 Boylston Street. Designed by Charles Luckman and Associates and Hoyle, Doran and Berry, 1959 4 7/8 x 3 3/8 Photographs